Gelfand-kirillov dimension of skew pbw extensions (2013)
Gelfand-Kirillov dimension of Poincaré-Birkhoff-Witt (PBW for short) extensions was established by Matczuk ([15], Theorem A). Since PBW extensions are a particular example of skew PBWextensions (also called σ-PBW extensions), the aim of this paper is to compute this dimension for these extensions and hence generalize Matczuk's results for several algebras which can not be classified as PBW extensions.